Cover Picture: On The Potential of Dynamic Nuclear Polarization Enhanced Diamonds in Solid‐State and Dissolution 13C NMR Spectroscopy (ChemPhysChem 17/2016). Issue 17 (5th September 2016) - Bretschneider, Christian O.; Akbey, Ümit; Aussenac, Fabien; Olsen, Greg L.; Feintuch, Akiva; Oschkinat, Hartmut; Frydman, Lucio
Abstract : The Front Cover picture illustrates that nano‐ and micro‐sized diamonds can be hyperpolarized under cryogenic conditions by using nitrogen‐based defects, leading to long‐lived polarizations. However, their subsequent in vivo uses are challenged by solubility problems. More information can be found in the Full Paper by L. Frydman and co‐workers onpage 2691 in Issue 17, 2016 (DOI:10.1002/cphc.201600301 .